Respuesta :
The answer is
For (x - 1)(x - 7) to equal 0, either (x - 1) or (x - 7) must equal ___0__ . The values of x that would result in the given expression being equal to 0, in order from least to greatest, are __1_ and ___7_ .
For (x - 1)(x - 7) to equal 0, either (x - 1) or (x - 7) must equal ___0__ . The values of x that would result in the given expression being equal to 0, in order from least to greatest, are __1_ and ___7_ .
Answer:
For (x - 1)(x - 7) to equal 0, either (x - 1) or (x - 7) must equal __0___ . The values of x that would result in the given expression being equal to 0, in order from least to greatest, are _1__ and __2__
Explanation:
1) For (x - 1) (x - 7) = 0 one of the factors must equal zero because, 0 * (x - 7) = 0 and (x -1) * 0 = 0
2) The values of x that would result in (x - 1) (x - 7) = 0 are determined by doing the factors equal to 0:
x - 1 = 0 => x = 1
x - 7 = 0 => x = 7
Therefore the answer, in order from least to greatest, is: 1 and 7.
For (x - 1)(x - 7) to equal 0, either (x - 1) or (x - 7) must equal __0___ . The values of x that would result in the given expression being equal to 0, in order from least to greatest, are _1__ and __2__
Explanation:
1) For (x - 1) (x - 7) = 0 one of the factors must equal zero because, 0 * (x - 7) = 0 and (x -1) * 0 = 0
2) The values of x that would result in (x - 1) (x - 7) = 0 are determined by doing the factors equal to 0:
x - 1 = 0 => x = 1
x - 7 = 0 => x = 7
Therefore the answer, in order from least to greatest, is: 1 and 7.